(untitled) (Global Journal of Human-Social Science, 2021)
This research aimed to discover the contribution of competencies in the formation/development of a teacher’s emotional intelligence or EQ. In this quanitative research with a survey, 36 out of 40 teachers in SMP X in Indramayu, West Java, Indonesia participated as the sample. Methods of data analysis used simple correlation and regression analysis. The results showed that: a) there was a positive and strong correlation between teachers’ EQ and teachers’ competencies (correlation coefficient R = 0.730), indicating that the higher the competencies of a teacher, the higher the emotional intelligence. b) Competencies contributed to 53.2% of the construction/development of teachers’ emotional intelligence, while the remaining 46.8% referred to other factors (external factors). c) Teachers’ EQ level can be improved by enhancing teachers’ competencies (pedagogical, personal, and social competencies). d) Enhancement of teachers’ competencies, including pedagogical, personal, or social competencies, should be continuous to better their’ emotional intelligence, thus preparing them to deal with rapid changes in the educational environment.